Assemblages of saprophagous muscids (Diptera: Muscidae) in three urban sites of temperate Argentina - Patitucci, Luciano Damián (2013)
Muscidae occupy a great diversity of habitats and trophic niches. In temperate environments, the knowledge of ecological aspects of saprophagous muscids is fragmentary. The aim of this work was to characterize the assemblages of saprophagous muscids regarding their richness and abundance, bait preference, heliophily, and seasonality of species in three sites with different urbanization levels sampled during two years in an area of temperate Argentina. A total of 3,321 specimens belonging to 20 species were collected. The baits and microhabitat preferences, and seasonal fluctuation of species were described. An increase in diversity in terms of evenness and richness in less urbanized sites was observed. Results support the hypotheses about sites with an intermediate urbanization, which contain major landscape heterogeneity, show a higher number of species. The assemblage response regarding the environment types reflects the adaptability to the physical changes along the three sites with different degree of urbanization.